Exploring molecular portraits defining lymphovascular invasion in invasive breast cancer patients - Sonbul, Sultan Naeem M. (2019)
BACKGROUND: Lymphovascular invasion (LVI) is a robust clinicopathological parameter of poor prognosis in invasive breast cancer (BC). The accurate detection of tumour emboli within lymphovascular cavities in invasive BC can predict the unfavourable outcome for BC patients, including distant metastasis, recurrence, and short survival. The molecular drivers of LVI in invasive BC patients remain poorly defined. We sought to determine if specific transcriptomic and proteomic profiles regulate the LVI mechanisms in invasive BC.